Structural change and productivity growth : a review with implications for developing countries - Isaksson, Anders (UNIDO ViennaAT, 2010)
Discusses the methods commonly used for the quantification of a sector's productivity performance and describes how these methods have evolved over time, as more detailed firm-level information has become available. Discusses some limitations of the methods and results presented. Offers a suggestion as to why the conclusions may be biased. Proposes a solution.